Effective sports coaching: A systematic integrative review - Mills J. P.; Clements , K. (SportRxiv Preprints, 2021)
Research investigating coaching effectiveness is of great importance to ensure the sporting experience and development of athletes is optimised. Coaches are significant figures for the athletes they coach, especially for youth athletes within sporting programmes. Therefore, understanding what makes an `effective coach` in terms of leadership and coaching behaviours will only aid positive youth development and help ensure youth athletes are afforded optimal opportunities to enhance their skills and attributes. This systematic review aims to present a comprehensive review of the coaching effectiveness literature. A systematic search was conducted of four electronic databases: PsycArticles, PsycINFO, SPORTDiscus, and Web of Science. Scholarly peer-reviewed studies published in English were included in this review. The initial search yielded 137 papers, with 45 papers retained and referenced within the review following screening. Studies either developed a measurement tool to assess coaching behaviour, evaluated a measurement tool, or employed such tools in studies assessing sources, dimensions or outcomes of coaching behaviour. Overall, the review offers support for the importance of athletes` perceptions of coaching behaviours in shaping an athletes` psychological development and well-being. Understanding athlete perceptions of effective coaching behaviours and how they impact specific outcomes may help to improve positive development in youth athletes.